Exposure to multiple parasites is associated with the prevalence of active convulsive epilepsy in sub-Saharan Africa - Kamuyu, G; Bottomley, C; Mageto, J; Lowe, B; Wilkins, P; Noh, J; Nutman, T; Ngugi, A; Odhiambo, R; Wagner, R; Kakooza-Mwesige, A; Owusu-Agyei, S; et al. (Public Library of Science, 2014)
BACKGROUND: Epilepsy is common in developing countries, and it is often associated with parasitic infections. We investigated the relationship between exposure to parasitic infections, particularly multiple infections and active convulsive epilepsy (ACE), in five sites across sub-Saharan Africa. METHODS AND FINDINGS: A case-control design that matched on age and location was used. Blood samples were collected from 986 prevalent cases and 1,313 age-matched community controls and tested for presence of antibodies to Onchocerca volvulus, Toxocara canis, Toxoplasma gondii, Plasmodium falciparum, Taenia solium and HIV. Exposure (seropositivity) to Onchocerca volvulus (OR = 1.98; 95%CI: 1.52-2.58, p<0.001), Toxocara canis (OR = 1.52; 95%CI: 1.23-1.87, p<0.001), Toxoplasma gondii (OR = 1.28; 95%CI: 1.04-1.56, p = 0.018) and higher antibody levels (top tertile) to Toxocara canis (OR = 1.70; 95%CI: 1.30-2.24, p<0.001) were associated with an increased prevalence of ACE. Exposure to multiple infections was common (73.8% of cases and 65.5% of controls had been exposed to two or more infections), and for T. gondii and O. volvulus co-infection, their combined effect on the prevalence of ACE, as determined by the relative excess risk due to interaction (RERI), was more than additive (T. gondii and O. volvulus, RERI = 1.19). The prevalence of T. solium antibodies was low (2.8% of cases and 2.2% of controls) and was not associated with ACE in the study areas. CONCLUSION: This study investigates how the degree of exposure to parasites and multiple parasitic infections are associated with ACE and may explain conflicting results obtained when only seropositivity is considered. The findings from this study should be further validated.